Women in small-scale agricultural production in Trinidad. Report on a survey of five groups as part of the IICA project: Enhancing the participation of women in the rural development process in Trinidad and Tobago through institutional strengthening - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
70 páginas